Implementasi dan Evaluasi Layanan Bimbingan Komprehensif pada Anak Sekolah Dasar: Studi Berdasarkan Empat Aspek Utama - Yulyany, Fidyah Suci; Roni, Vidya Asyilah; Rizkya, Anna Nabila; Agustin, Lutfia Sri; Nurshifa, Sella; Akbar, Royan; Lestari, Triana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the implementation and evaluation of comprehensive guidance services for elementary school children based on four main aspects. This study uses a qualitative approach with a participatory method. The subjects of the study were those who were directly involved in the phenomenon analyzed totaling 26 people. The data collection method was carried out through participant observation, interviews, and group discussions. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of comprehensive guidance services for elementary school students has a significant impact on student development in four main aspects, namely academic, social, personal, and career